Retalho de rotação para defeitos da asa nasal - Pontes, Luciana Takata; Kimyai-Asadi, Arash; Jih, Ming H.; Moraes, Aparecida Machado; Stolf, Hamilton Ometto [UNESP] (My University, 2009)
Surgical defects of the alar lobule can be difficult to repair with functional and aesthetically desirable results. Skin grafts are smoother and paler than the nasal skin. Flaps from the cheek and proximal nose can bridge the alar crease, resulting in obstruction. The authors describe a technique to repair nasal ala defects, with maintenance of the cosmetic unit, without airflow disturbance.
Rotation flaps for nasal alar defects
Keywords: Nasal obstruction; Nose; Reconstruction; Skin transplantation; Surgical flaps